Synthesis Characterization and Antimicrobial Studies of Zn(II), Cu(II), Pb(II), Ni(II) and Co(II) Complexes of 3-(4’-Sulfamoyl iminophenyl) Isatin - SUBUDHI, B.B.; SUDHIR KUMAR, P.; GHOSH, G. (Asian Journal of Chemistry, 2010)
Carbonic anhydrase inhibitors are widely reported with antimicrobial action. The antibacterial actions of sulfanilamide and isatin are found to be enhanced on complexation with metals. Considering this Zn(II), Cu(II), Pb(II), Ni(II) and Co(II) complexes of 3-(4’-sulfamoyl iminophenyl) isatin were synthesized and evaluated against some urinary tract pathogens. The Cu(II) complex was found to be most potent against the pathogens.